2010
DOI: 10.2147/ijwh.s6938
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of post-partum depression: a review of clinical, psychological and pharmacological options

Abstract: Postpartum depression (PPD) is a common complication of childbearing, and has increasingly been identified as a major public health problem. Untreated maternal depression has multiple potential negative effects on maternal-infant attachment and child development. Screening for depression in the perinatal period is feasible in multiple primary care or obstetric settings, and can help identify depressed mothers earlier. However, there are multiple barriers to appropriate treatment, including concerns about medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 144 publications
(162 reference statements)
1
70
0
2
Order By: Relevance
“…Notably, decreases in women’s depression scores were inversely correlated with increases in their serum estrogen levels, and available data suggest that estradiol therapy was well tolerated with low dropout rates. However, estradiol therapy may interfere with breastfeeding, a consideration important in the treatment of PPD (Fitelson et al, 2010; Moses-Kolko et al, 2009). Although early data suggested that synthetic progesterones may be therapeutic for PPD, this view has since been challenged and the use of progesterones is not recommended (Dennis et al, 2008).…”
Section: Current Treatment Of Postpartum Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, decreases in women’s depression scores were inversely correlated with increases in their serum estrogen levels, and available data suggest that estradiol therapy was well tolerated with low dropout rates. However, estradiol therapy may interfere with breastfeeding, a consideration important in the treatment of PPD (Fitelson et al, 2010; Moses-Kolko et al, 2009). Although early data suggested that synthetic progesterones may be therapeutic for PPD, this view has since been challenged and the use of progesterones is not recommended (Dennis et al, 2008).…”
Section: Current Treatment Of Postpartum Depressionmentioning
confidence: 99%
“…Several meta-analyses exist to date and suggest that psychological interventions are efficacious in reducing depressive symptoms (Cuijpers et al, 2008; Dennis and Hodnett, 2007; Lumley et al, 2004; Sockol et al, 2011) at rates similar to those of antidepressant medications (De Crescenzo et al, 2013; Sockol et al, 2011). No conclusive data exist to suggest the superiority of one psychotherapy modality to another in the treatment of PPD (Fitelson et al, 2010), although there is some evidence that IPT, which directly addresses interpersonal problems (e.g., role transitions, relational conflicts), may be more efficacious than CBT, which targets maladaptive depressogenic cognitions (Bledsoe and Grote, 2006; Sockol et al, 2011). …”
Section: Current Treatment Of Postpartum Depressionmentioning
confidence: 99%
“…Sleep disturbances can also lead to negative consequences, such as dysphoric mood and impaired cognitive function, while persistent difficulty with concentration or cognitive tasks is indicative of a mood disorder [ 7 ]. Substance abuse and medical causes of psychiatric symptoms, such as thyroid disorders, should also be considered [ 8 ]. The “baby blues” is a transient mood disturbance that can affect as many as 70% of new mothers within ten days of delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum depression is an increasingly recognized public health problem with far-reaching consequences for both infants and mothers (Fitelson et al 2010). Changes in sleep have been hypothesized as a modifiable risk factor for the development of postpartum depression.…”
Section: Introductionmentioning
confidence: 99%